Receptor activity‐modifying protein‐dependent effects of mutations in the calcitonin receptor‐like receptor: implications for adrenomedullin and calcitonin gene‐related peptide pharmacology. (13th January 2014) - Watkins, H A; Walker, C S; Ly, K N; Bailey, R J; Barwell, J; Poyner, D R; Hay, D L
Abstract : Background and Purpose: Receptor activity‐modifying proteins (RAMPs) define the pharmacology of the calcitonin receptor‐like receptor (CLR). The interactions of the different RAMPs with this class B GPCR yield high‐affinity calcitonin gene‐related peptide (CGRP) or adrenomedullin (AM) receptors. However, the mechanism for this is unclear. Experimental Approach: Guided by receptor models, we mutated residues in the N‐terminal helix of CLR, RAMP2 and RAMP3 hypothesized to be involved in peptide interactions. These were assayed for cAMP production with AM, AM2 and CGRP together with their cell surface expression. Binding studies were also conducted for selected mutants. Key Results: An important domain for peptide interactions on CLR from I32 to I52 was defined. Although I41 was universally important for binding and receptor function, the role of other residues depended on both ligand and RAMP. Peptide binding to CLR/RAMP3 involved a more restricted range of residues than that to CLR/RAMP1 or CLR/RAMP2. E101 of RAMP2 had a major role in AM interactions, and F111/W84 of RAMP2/3 was important with each peptide. Conclusions and Implications: RAMP‐dependent effects of CLR mutations suggest that the different RAMPs control accessibility of peptides to binding residues situated on the CLR N‐terminus. RAMP3 appears to alter the role of specific residues at the CLR‐RAMP interface compared with RAMP1 and RAMP2.